STUDY OF THE DESIGN OF NATIONAL PARK OF HALABJA (PAYTAKHTY ASHTY) ACCORDING TO THE ENVIRONMENTAL AND RECREATIONAL NEEDS OF THE RESIDENTS - Sharbazhery, Ali O. M.; Mustafa, Mihraban O.; Rashid, Chia K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Designed a national park in the name of Peace Park (Paytakhty Ashty) on an area of 25 hectares of agricultural land with a slope of 1-2 %, located at latitude N35°11’’42 and longitude E46°1’’18, at an altitude of 780 m from sea level, in the north-eastern side of Halabja city, which is one of the oldest cities in Kurdistan, Iraq, which is located in the plains of Shahrazur, which is the second most fertile soil in the world, then the Halabja city became a symbol of peace because of its genocide and was named the capital of peace , so the designed park it named the Peace Park. The designs for the park site were developed according to the suitability of the site and its surroundings and its topography, as well as a study of the environmental factors of the area, so that the most important negative aspects of the climate were taken into account due to the lack of humidity (17%) and high temperature (49°C) during the summer months and the opposite during the winter months (-6°C) and at the same time the presence of comfort zone during the spring and autumn months. The opinions of part of the residents, specialists in the municipality and academics in this field were also taken into consideration in the design process, as 100% of the respondents see the necessity of having a national park in their city, 61% of them like to visit the park weekly and the preferred time to visit is 62% in the afternoon, while the preferred forms of visit are collective, such as friends and families, and with a percentage of 88% of the respondents. The most preferred recreational activities in the park are sitting and resting, watching beautiful scenery (100%), children’s games (95%), special places for families (94%), saliva city, sports arenas, hiking and nature tours, respectively.